1983
DOI: 10.1177/0022002183014003009
|View full text |Cite
|
Sign up to set email alerts
|

Social Loafing in Cross-Cultural Perspective

Abstract: Research conducted in the United States indicates that people exert greater effort in a variety of task situations when they perform individually than when they do so in a group that obscures identifiability of members' individual outputs, a phenomenon termed "social loafing." It was hypothesized that members of cultures whose value emphases and social institutions have been characterized as "group-oriented" would tend to form more cohesive groups and be more likely to place group benefit over individual benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 8 publications
0
15
0
1
Order By: Relevance
“…Asians are often less inclined to loaf than are North Americans (Karau & Williams, 1993). Gabrenya, Wang, and Latane (1983), for example, found that Taiwanese schoolchildren performed better on a clapping and shouting task when working in a group than when working individually. Similarly, Earley (1993) compared Chinese, Israeli, and North American trainees' endorsement of collectivist versus individualistic orientations and their performance on a simulated ‘in‐basket’ office task.…”
Section: Moderating Effects Of Chinese Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Asians are often less inclined to loaf than are North Americans (Karau & Williams, 1993). Gabrenya, Wang, and Latane (1983), for example, found that Taiwanese schoolchildren performed better on a clapping and shouting task when working in a group than when working individually. Similarly, Earley (1993) compared Chinese, Israeli, and North American trainees' endorsement of collectivist versus individualistic orientations and their performance on a simulated ‘in‐basket’ office task.…”
Section: Moderating Effects Of Chinese Culturementioning
confidence: 99%
“…Chinese trainees, however, typically performed better when working in a group of similar others than when working either individually or with strangers. Earley (1993) and also Gabrenya et al. (1983) attributed this cross‐cultural difference in part to the different norms and values that predominate in North American and Asian societies.…”
Section: Moderating Effects Of Chinese Culturementioning
confidence: 99%
“…Die Aufgabenstellung für die Probanden besteht darin, dass jeweils drei Personen gemeinsam mit den ihnen zur Verfügung stehenden Löschgeräten (Feuerwehrautos und Hubschrauber) einen Flächenbrand bekämpfen müssen, der in bestimmten Segmenten auf der Bildschirmoberfläche ausbricht. In Anlehnung an Steiners Taxonomie handelt es sich beim gemeinsamen Bekämpfen der Feuer um eine additive Optimierungsaufgabe (Steiner 1972 (Comer 1995;Earley 1989;Gabrenya et al 1983Gabrenya et al , 1985Williams, Nida, Baca und Latané 1989 (Karau und Williams 1993, 1995Shepperd 1993 (Duval und Wicklund 1972, 1973Wicklund 1975). Beim Lösen des komplexen Problems wird dieser Leistungsstandard nicht so einfach erzielt, weshalb sich Personen umso mehr anstrengen.…”
Section: Das Szenario Networked Fire Chiefunclassified
“…Analogously, the social-loafing effect seemed a good candidate for a universal process, but that is not what has been found (Gabrenya, Latané, & Wang, 1983;Gabrenya, Wang, & Latané, 1985 …”
Section: Notesmentioning
confidence: 93%